2017
DOI: 10.1140/epjd/e2017-70829-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation, Breit and Quantum Electrodynamics effects on energy level and transition properties of W54+ ion

Abstract: Abstract. The electron correlation effects and Breit interaction as well as Quantum Electro-Dynamics (QED) effects were expected to have important contribution to the energy level and transition properties of heavy highly charged ions. The ground states [Ne]3s 2 3p 6 3d 2 and first excited states [Ne]3s 2 3p 5 3d 3 of W 54+ ion have been studied by using Multi-Configuration Dirac-Fock method with the implementation of Grasp2K package. A restricted active space was employed to investigate the correlation contri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…And some transitions with wavelength in 18. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].6Å are suggested to be observed in the future experiment.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…And some transitions with wavelength in 18. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].6Å are suggested to be observed in the future experiment.…”
Section: Introductionmentioning
confidence: 73%
“…According to the synthetic spectrum there are only 3 peaks that would be observed in the EBIT experiment with this condition, namely, the transition lines with key 1, 5, and 20 in Fig. 2(b), These 3 peaks are regarded as the E1 transi- 19.260Å and 18.590Å, respectively. The lower part Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Beginning with basic atomic structure, the work of Ding et al [1] on the energy levels and transition probabilities of the 54-times ionized tungsten ion W 54+ shows that relativistic and quantum electrodynamic corrections make an important contribution in these heavy highly-ionized ions, and must be taken into account to get physically significant results. This result can generally be expected to be true for all heavy ions, and so comparisons with experiment are important.…”
Section: Summary Of Contributionsmentioning
confidence: 99%
“…Many research works on the radiative properties of tungsten ions related to fusion in various ionization stages have been published in the past several decades [5][6][7][8][9][10][11][12][13]. Special attention has been paid to the magnetic dipole (M1) transitions of the W 54+ ion [14][15][16][17][18][19][20][21][22][23]. In their electron beam ion trap (EBIT) experiment, Ralchenko et al [14] observed two emission peaks at 14.986 nm and 17.144 nm, which they identified with M1 transitions between the levels of the ground configuration [Ne]3s 2 3p 6 3d 2 of W 54+ .…”
Section: Introductionmentioning
confidence: 99%